TARI TOPENG SEKARTAJI ONĔNG HASIL REINTERPRETASI TARI TOPENG SEKARTAJI TUNGGAL KARYA SULISTYO HARYANTI - Puspitaningrum, Windri Estri; Sulastuti, Katarina Indah (Greget : Jurnal Kreativitas dan Studi Tari, 2023)
The Sekartaji Tunggal Mask dance by Sulistyo Haryanti is an interpretation of the SekartajiMask fragment which was reinterpreted to become the Sekartaji Onĕng Mask dance. This studyanswers the problems of (1) the form of the Sekartaji Tunggal Mask dance, (2) the process and resultsof the reinterpretation of the Sekartaji Tunggal Mask dance by Sulistyo Haryanti to become theSekartaji Onĕng Mask dance. The method used in this qualitative research is descriptive analytics.In discussing the problem of form, the concept of form is used by Katarina Indah Sulastuti that formis related to dance or choreographic compositions which include interrelated elements, includingmotion, make-up, dance music, floor patterns, dramatic designs, properties, place and time ofperformance. Dharsono Sony Kartika discussed the reinterpretation of art that conceptually tries toreinterpret traditional art forms. By following with modern techniques and the artist's style ofexpression individually in expressing ideas, the creation of works of art can reinterpret traditionalart idioms, as a model of conservation, and development, or also known as cultural personalexpression. The results showed that the form of the Topeng Sekartaji Tunggal dance by SulistyoHaryanti uses the movements of the developed bedhaya and srimpi dances. The music for the dancerefers to Fragmen, the clothing used refers to the character Sekartaji, the floor pattern uses straightand curved lines. The process and results of the reinterpretation produce the Topeng Sekartaji Onĕngdance through the stages of preparation, exploration, improvisation, the training process, thestabilization/rehearsal stage and the reinterpretation results are carried out in the motion of the mask,the dance music adds songs and monologues. Corrective makeup uses a paes style mask with a dodotklembrehan dress. The dramatic design is reinterpreted with 5 peak points towards the climax and 4descending points, the floor pattern emphasizes the curved line pattern.